Lifelong Learning in Modern Strategies of Sustainable Development - Voitovska, Oksana; Tolochko, Svitlana; Bordyug, Nataliya (Studia Warmińskie, 2018)
Due to the plasticity and dynamics of modern socio-cultural life, it can be noted that education is now presented as an open system, i.e. one in which it is impossible to propose certain permanent and unchanging solutions. According to the authors of the article, this means that the variability and dynamics of social, economic, psychological or environmental problems determines the necessity for the modern man to take the so-called. lifelong learning. The authors emphasize that the implementation in the societies of the process of lifelong learning in the current socio-cultural conditions will be conducive to the sustainable development of both the entire humanity and individual communities.